Effect of methanolic extract of Achyranthes aspera on allergy induced by potassium dichromate - Londonkar, Ramesh; V, Chinnappa Reddy; Kamble, Abhaykumar (Recent Research in Science and Technology, 2013)
Potassium dichromate and other Cr (vi) forms are found as potent allergen in metal industries, cement industries where constant contact and inhalation or ingestion occurs which tend cause severe allergy. Several medicinal plants have potent anti allergic effects and drugs from natural products are free from side effects. The present study was aimed to evaluate the utility of Achyranthes.aspera in treating allergies caused due to heavy metals, particularly dichromate in albino mice. The allergy was induced in mice by giving oral administration of K2Cr2O7 at a concentration of 200mg/kg body weight for the period of 10 days. The diagnosis of allergy was done by serum analysis of IgM and IgG antibodies, total Lymphocytic count and total WBC count. The methanolic extract of A.aspera (400mg/kg, 600mg/kg body wt) showed greater efficiency in reducing the effects of dichromate allergy induction.